Revenue Cycle Effectiveness Through Internal Control Evaluation with Coso Framework - Safitri, Anni; Sari, Fangela Myas (Journal of Social and Policy Issues, 2025)
Problems In a business, of course, it cannot be separated from problems. Likewise with Yuanna Catering in Mayong, there are problems in two main activities, namely catering for parties and catering for employees. This research method uses a qualitative approach using a research object in the form of a business entity, namely Yuanna Catering. method with analysis using the COSO Internal Control perspective The purpose of this study is to determine how the internal control implemented can overcome problems and risks that arise in a business entity. The purpose of this study is to increase the effectiveness of the revenue cycle at Yuanna Catering in Mayong through the design of internal control with the COSO internal control framework. The results obtained in the business entity indicate that this medium-scale agency service business still has weak internal control. The business entity understands what problems and risks exist, but has not been able to overcome the problems and risks that arise optimally. Keywords: Internal Control, COSO Framework, Revenue Cycleproblems and risks that appear to maximally.